PTH-085 Deoxythioguanosine (DTG) in DNA as a Pharmacological Endpoint of Thiopurine Treatment in Inflammatory Bowel Disease Patients. (17th August 2016) - Coulthard, S; Berry, P; McGarrity, S; Kobayashi, T; Toyonaga, T; Ansari, A; Redfern, C
Abstract : Introduction: We have used a sensitive assay to measure incorporated dTG in the DNA isolated from peripheral blood cells of patients treated with thiopurines with the aim of identifying a more appropriate pharmacological marker of response for patients on therapy with the thiopurines azathioprine (AZA) or mercaptopurine (MP). Methods: DNA was isolated from blood samples collected from 38 IBD patients; 23 on AZA and 15 on MP. DNA was denatured, digested using P1 nuclease followed by treatment with alkaline phosphatase and finally diluted in MilliQ water prior to analysis. A total of 0.2 µg of DNA in 50 µL was injected for chromatographical separation followed by analysis on an API4000 triple quadrupole LC-MS/MS. Standard curves and controls were validated and samples analysed to determine number of moles of dTGN/ 105 5 moles of dA. Results: A cohort of patients with Crohn's Disease (CD) on AZA (n = 11) or MP (n = 5) or Ulcerative Colitis (UC); AZA (n = 12), MP (n = 10) established on thiopurine therapy for more than 25 weeks and in clinical remission were analysed. For those on AZA only there was a statistically significant correlation between dTG levels and AZA dose (Kendall Rank correlation, P < 0.05; median =0.89, mean = 2.03, SD = 2.92; range 0.0–11.3); however there was no such correlation for the MP treated patients (Kendall Rank correlation, P > 0.05; median =1.05, mean = 1.0, SD = 1.0; range 0.0–3.3). When disease was taken into account there was no statistical difference in dTG levels between those taking AZA (Mann-Whitney, P > 0.9; for CD patients, median =0.89, mean = 2.13, SD = 3.34; for UC patients, median =1.11, mean = 1.19, SD = 2.61). However, for those taking MP there was a statistically-significant difference (Mann-Whitney, P < 0.05; for CD patients, median =1.7, mean = 1.98, SD = 0.99; for UC patients, median =1.45, mean = 0.59, SD = 0.63) Conclusion: This pilot study shows that the levels of dTG in treated patients are similar whether the patients are on AZA (average dose 118 mg) or MP (average dose 39 mg equivalent to approximately 81 mg AZA). However, there were clear differences between the two drug-treatment groups with respect to the correlation of dTG and drug dose and in the relationship between dTG incorporation and disease type. These results justify a larger cohort study to investigate the role of drug-DNA interactions in clinical responses to thiopurines Disclosure of Interest: None Declared